Case report: Dual dabrafenib and trametinib therapy for treating BRAF V600E mutated lung adenocarcinoma with BRCA2 germline mutation post multiline progression - Zhang, Huimin; Cong, Xiaofeng; Yin, Jiaxin; Chen, Chen; Liu, Ziling (Frontiers in Oncology, 2024)
The v-raf murine sarcoma viral oncogenic homolog B1 (BRAF) V600E is a rare mutation that functions as an oncogenic driver in patients with non-small cell lung cancer (NSCLC) leading to the overactivation of the RAS-RAF-MEK-ERK (MAPK) pathway and the subsequent uncontrolled cell proliferation. Understanding the mechanism behind BRAF mutation, its inhibition, and relationship to the upstream and downstream effector is essential for advancing treatment strategies for NSCLC patients with the BRAF V600E mutation. Next-generation sequencing studies have identified the presence of breast cancer susceptibility gene 1/2 (BRCA1/2) mutations in NSCLC patients, which are pathogenic variants associated with breast, ovarian, and prostate cancers. Although poly ADP-ribose polymerase (PARP) inhibitors are currently an approved treatment option for malignant tumors linked to BRCA1/2 pathogenic variants, the therapeutic potential of PARP inhibitors in NSCLC remains unclear. The development of genetic testing provides a platform for investigating the pathophysiological mechanisms of genetic mutations above. Here, we report a novel case of a middle-aged non-smoking female diagnosed with BRAF V600E and BRCA2 germline mutated lung adenocarcinoma, who had previously undergone a diverse array of cancer-targeted therapies, including PARP inhibitor, before the identification of the BRAF V600E mutation. Following this, a combination of dabrafenib and trametinib was administered and induced a rapid and positive response within two months. Our case not only highlights the importance of dynamic and repetitive genetic testing in managing patients, but contributes to the growing body of clinical evidence supporting the efficacy of BRAF/MEK co-inhibition in patients harboring a BRAF V600E mutation and provokes thinking for further research into the impact of PARP inhibitors in BRCA1/2-mutated NSCLC.